Stability of watermelon phenotype characters (Citrullus lanatus (Thunb.) Matsum. & Nakai) from crossing ♀ ‘Putri Delima’ with ♂ ‘Maduri’ - Deris Trian Rahmandhias; Wiko Arif Wibowo; Aprilia Sufi Subiastuti; Budi Setiadi Daryono (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2021)
Watermelon (Citrullus lanatus (Thunb.) Matsum. & Nakai) is a horticultural plant that belongs to the Cucurbitaceae family with high public demand, however, local markets sometimes have limited supply. The existence of watermelon varieties that are not pest-resistant causes its production to be erratic. Therefore, plant breeding efforts are required to produce superior varieties through the stability test of plant characters. For watermelon to be certified as a new variety, it needs to possess a stable and adaptive character to various conditions. The F1 watermelon from crossing ♀ ‘Putri Delima’ with ♂ ‘Maduri’ produces inole-shaped fruit, red flesh, and a sweet taste. Therefore, this study aims to determine the stability of the phenotypic character of watermelon F2 from crossing ♀ ‘Maduri’ with cultivar ♂ ‘Putri Delima’ and was conducted in Jamusan, Bokoharjo, Prambanan, Sleman, D.I.Yogyakarta fields from August to December. There are five samples of ripe watermelons that were selected randomly while their phenotypic characters were observed qualitatively and quantitatively. Each F2 watermelon character was compared to F1, and the quantitative analysis was conducted using one-factor ANOVA with a confidence level of 5%. The results of quantitative character analysis between F2 and F1 showed a P (P-value)> 0.05. Meanwhile, the results of qualitative observations of F2 watermelon showed different flesh and skin color, while the harvest time from F1 was caused by the segregation of heterozygous crosses. Therefore, it is necessary to select superior phenotypic characters as desired for the next breeding.